A case of IgG4-related tubulointerstitial nephritis and membranous glomerulonephritis during the clinical course of gastric cancer: Imaging features of IgG4-related kidney disease. Issue 3 (4th May 2019) - Horita, Shigeto; Fujii, Hiroshi; Mizushima, Ichiro; Fujisawa, Yuhei; Hara, Satoshi; Yamada, Kazunori; Inoue, Dai; Nakajima, Kenichi; Harada, Kenichi; Kawano, Mitsuhiro
Abstract: We describe an 81-year-old man with immunoglobulin G4-related disease (IgG4-RD) presenting with submandibular gland, lymph node, lung, kidney, aortic wall, and prostate lesions with concomitant gastric cancer. After curative surgical treatment of the gastric cancer, corticosteroid therapy for progressively decreasing renal function was started. Before starting steroid therapy, fluorodeoxyglucose positron emission tomography-computed tomography revealed multiple lesions of IgG4-RD but no metastasis of the cancer. However, the patient died 3 months after initiation of corticosteroid therapy because of recurrence of the gastric cancer. In this case, the imaging features of IgG4-tubulointerstitial nephritis dramatically changed during the clinical course of co-existing gastric cancer. The imaging features of the present case may provide clues to the pattern of spread of IgG4 lesions in the kidney.